THE INFLUENCE OF SCHOOL AND FAMILY ENVIRONMENTS ON ACADEMIC ACHIEVEMENT OF GRADE X STUDENTS IN TECHNICAL DRAWING SUBJECT IN THE TKRO DEPARTMENT OF SMKN 7 SERANG - Pahrudin, Iip; Supriyatna, Deddy; Putra, Ananda Yhuto Wibisono Putra (Journal of Mechanical Engineering Education, 2025)
This study aims to determine the influence of school and family environments on student learning achievement in the subject of Engineering Drawing for class X TKRO at SMKN 7 Serang in the 2024/2025 academic year. The school environment includes physical, social, and academic aspects, while the family environment includes emotional support, supervision, and parental involvement. This study uses a quantitative approach with a survey method, involving all 31 class X TKRO students. Data were collected through a Likert scale questionnaire that had been tested for validity and reliability, as well as documentation of report card grades. Data analysis used the T test, F test, and multiple linear regression with the help of SPSS version 25. The results showed that neither the school environment nor the family environment had a significant effect, either partially or simultaneously, on student learning achievement. The coefficient of determination (R²) value of 0.086 indicates that the influence of the two variables is very low. This finding indicates that other factors such as learning motivation and learning strategies play a greater role in determining student achievement.